Rheumatoid factor, chronic arthritis and mortality. - Heliövaara, M (1995)
OBJECTIVE--To investigate chronic arthritis and rheumatoid factor (RF) for their prediction of premature total and cardiovascular mortality. METHODS--In 1978-80, a representative population sample of 8000 Finns aged 30 or more was invited to participate in a comprehensive health examination; 90% complied. Arthritis was diagnosed on the basis of medical history, symptoms, and physical examination. Serum RF was determined by the sensitised sheep cell agglutination test. RESULTS--By the end of 1992 1597 of the subjects had died from all causes, including 876 deaths from cardiovascular diseases. When adjusted for age, gender and smoking, the relative risk of persons with RF positive arthritis dying from any cause was 1.61 (95% confidence interval (CI) 1.03 to 2.51); RF negative non-erosive arthritis was not associated with mortality (relative risk 1.03; 95% CI 0.72 to 1.49). In the absence of arthritis, 'false positive' RF titres > or = 128 predicted cardiovascular deaths with a relative risk of 1.74 (95% CI 1.06 to 2.86). CONCLUSION--Both RF positive arthritis and false positive RF reactions predict mortality, but through different disease patterns.